Avaliação da expressão do vírus de Epstein-Barr e metaloproteinase 9 nas células de Hodgkin-Reed-Sternberg e correlação com os parâmetros clínicos e evolutivos em pacientes com Linfoma de Hodgkin clássico no Brasil - Souza, Eni Maria de [UNIFESP] (2010)
Clinical and histological features of classical Hodgkin lymphoma (cHL) are primarily due to the effects of cytokines, enzymes and chemokines produced by Hodgkin-Reed-Sternberg (HRS) cells and their surrounding inflammatory cells in response to signals triggered by etiological factors such as Epstein-Barr virus (EBV). Matrix metalloproteinase-9 (MMP-9) has been associated with poorer survival in patients with aggressive non-Hodgkin lymphomas. In EBV-related cancers the expression of viral latent membrane protein 1 (LMP1) correlates with an increased MMP-9 expression. In this study, we evaluated the prognostic relevance of MMP-9 expression and EBV status in HRS cells in patients with cHL in Brazil. Material and Methods: We selected 97 patients with cHL. Patients were included if they had: 1) > 18 years, 2) Undergone similar chemotherapy protocols, 3) Paraffin blocks available for review and for EBV and MMP-9 detection and 4) Clinical, epidemiological and laboratorial parameters available. Results: EBV was detected in 52.5% of all cases. MMP-9 expression positivity was found in 87.6% of all cases. There was no correlation between MMP-9 expression and EBV status. Response to treatment and relapse rate were independent of MMP-9 expression and EBV status. When stratified according to chemotherapy protocol used or disease stage, we still did not find any difference. MMP-9 positivity did not influence overall survival and event free survival. Conclusion: MMP-9 are expressed in the majority of HRS cells and did not correlated with EBV status or survival. The consistent MMP-9 expression in HRS cells makes this enzyme a potential target for therapy.